2021
DOI: 10.1155/2021/7362233
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanism by Which Curcumin Cooperates with Sestrin2 to Inhibit the Growth of Pancreatic Cancer

Abstract: Background. Pancreatic carcinoma is a malignant tumor with a high fatality rate, and the increased resistance of pancreatic carcinoma to chemotherapy has become a difficult problem in clinical practice. Hence, it is imperative to develop an effective treatment for pancreatic cancer. Sestrins are a class of stress-induced proteins that have antioxidation functions, regulating cell growth and metabolism. Curcumin is a natural pigment isolated from turmeric. Several studies have also suggested that this molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In addition to KIF20A, BAR502 potently downregulated the expression of the Ribonucleotide reductase subunit M2 (RRM2), (FC: -14,34) ( 68 ) and TNF Receptor Superfamily Member 1B (TNFRSF1B or TNFR2) (FC: -11,72) ( 69 ) and DNA topoisomerase II alpha (TOP2A) (FC: -9,61), an important regulator of DNA replication and cell cycle progression and up-regulated in PDAC ( 70 ). On the other hand, exposure to BAR502 increased the expression of a number of genes, including the Solute carrier family 7 member 11 (SLC7A11) (FC: 35,54), a cysteine transporter involved in the inhibition of the ferroptosis programmed cell death ( 71 ), that was the most upregulated gene, and the Cyclin D2 (CCND2) (FC: 16,13) ( 72 ) and Sestrin 2 (SESN2) (FC: 15,84) ( 73 ),, whose expression are robustly reduced in PDAC cells ( 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to KIF20A, BAR502 potently downregulated the expression of the Ribonucleotide reductase subunit M2 (RRM2), (FC: -14,34) ( 68 ) and TNF Receptor Superfamily Member 1B (TNFRSF1B or TNFR2) (FC: -11,72) ( 69 ) and DNA topoisomerase II alpha (TOP2A) (FC: -9,61), an important regulator of DNA replication and cell cycle progression and up-regulated in PDAC ( 70 ). On the other hand, exposure to BAR502 increased the expression of a number of genes, including the Solute carrier family 7 member 11 (SLC7A11) (FC: 35,54), a cysteine transporter involved in the inhibition of the ferroptosis programmed cell death ( 71 ), that was the most upregulated gene, and the Cyclin D2 (CCND2) (FC: 16,13) ( 72 ) and Sestrin 2 (SESN2) (FC: 15,84) ( 73 ),, whose expression are robustly reduced in PDAC cells ( 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are insufficient studies on curcumin cooperating with the sestrin family to inhibit tumors, and the mechanism is still unclear. A study carried out (193) observed the potential anticancer effects of curcumin combined with the sestrin family on pancreatic carcinoma and probe its possible molecular mechanisms. The results revealed that curcumin cooperated with sestrin2 to significantly suppress pancreatic cancer.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…In addition, sestrin2 cooperated with curcumin to inhibit pancreatic cancer by specifically targeting Nrf2/Keap1/HO-1/NQO-1. It is concluded that curcumin-mediated synergistic targeting of sestrin2 is a potentially valuable treatment for pancreatic cancer (193). In another study, a solid phase approach was proposed for the combinatorial synthesis of a mini library of the mimics of curcumin in good purity and yield.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Meanwhile, Sestrin2 expression decreases in higher stages of the tumor and positively correlates with patients’ survival [ 116 ]. Furthermore, lentiviral-mediated upregulation of Sestrin2 has been associated with inhibition of pancreatic cancer cells proliferation, invasion, and migration in PANC-1 and CFPAC-1 cell lines [ 117 ].…”
Section: Protective Effect Of Sestrin2 Against Cancermentioning
confidence: 99%